ANALYZING ATTRIBUTES THAT AFFECT CONSUMER PREFERENCE ON BOARDING HOUSE SELECTION AMONG WORKERS IN WIYUNG, SURABAYA: A CONJOINT ANALYSIS APPROACH - Jovan Angelo; Agustiono (RADJA PUBLIKA, 2026)
Rapid urbanization and population growth in Wiyung Surabaya, have increased the demand for boarding houses as an affordable housing option for workers, resulting in greater competition among boarding house providers. This study aims to identify workers’ preferences for boarding house attributes using conjoint analysis based on Random Utility Theory (RUT). Data were collected through an online questionnaire distributed to workers who were currently residing in or searching for boarding house accommodation in Wiyung, Surabaya. A total of 100 valid responses were analyzed. The study examined five attributes: environmental cleanliness, price, security (CCTV), bathroom type, and room size. The findings indicate that the most preferred boarding house profile includes total cleaning services, a monthly rental price of IDR 1.500.000 – IDR 2.000.000, CCTV provision, an indoor bathroom, and a room size of 3 × 6 meters. Overall, affordability, cleanliness, security, and supporting facilities were found to be the most influential factors in workers’ boarding house selection decisions. The findings provide practical insights for boarding house owners in designing accommodation offerings that better align with workers’ preferences.